KEMAMPUAN MENENTUKAN PREPOSISI DALAM KARANGAN DESKRIPSI SISWA KELAS VII MTs AL-ISTIQOMAH TEBINGTINGGI KABUPATEN KEPULAUAN MERANTI - Rismita, Lili; Sinaga, Mangatur; Hakim, Nursal (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This research entitled Ability to Determine Preposition in Essay Student Description Class VII MTs AL-Istiqomah Tebingtinggi Regency of Meranti Island. This study aims to determine what level of ability to determine the preposition of students of class VII MTs AL-Istiqomah Tebingtingggi Meranti Islands District. The type of this research is descriptive research. The study had a population of 38 and a sample of 38 using a saturated sample. The research data was obtained from the test result by the students completing the sentence that was in overview in the description text with 22 prepositions that have been provided. Data collection techniques in this research is a stuffing test technique. Data analysis techniques in this study make code, correct student test results, analyze errors based on Chaer theory, explain the results, and draw conclusions based on assessment categories. The results of research in this study is the student has not been able to determine the preposition in the essay description accurately so categorized failed.Keywords: Ability, preposition, essay description